ANALISIS PENGENDALIAN KUANTITAS PERSEDIAAN BAHAN BAKU GAS ARGON PADA PT. XY - Sinaga, Inggrid Wahyuni; Rapika, Aulia Dwi (Pusat P2M Politeknik Negeri Batam, 2023)
The background in this research is that there is no method used to manage and control the quantity of raw material supplies at PT XY. This situation causes problems in ordering raw materials so that ordering costs and costs for storage will not be optimal. The purpose of this study was to determine the effect of applying the EOQ method to the total cost of raw material inventory at PT. XY. Raw material inventory costs can be minimized by applying the EOQ (Economic Order Quantity) method. This method can show the economic order quantity, optimal purchase frequency, time to reorder/ROP (Re-Order Point), and the amount of safety stock. Data collection was carried out using documentation techniques related to observation inventory documents and interviews with several informants, for data analysis using EOQ by calculating total inventory cost, ROP, reorder frequency and safety stock. The results of calculations and data analysis using the EOQ method show that the total cost of inventory is lower than the company's actual method.